3rd IEEE International Symposium on Biomedical Imaging: Macro to Nano, 2006.
DOI: 10.1109/isbi.2006.1624982
|View full text |Cite
|
Sign up to set email alerts
|

Phase Stability Technique for Inverse Scattering in Optical Coherence Tomography

Abstract: We present a technique for maintaining phase stability in a three-dimensional optical coherence tomography system. When determining the inverse scattering solution, phase stable measurements are required to ensure proper object reconstruction. The proposed method uses a reference object placed above the specimen to facilitate the retrieval of accurate constant phase surfaces throughout the specimen. Our algorithm locates the reference object, determines the phase and group delay, and corrects the phase disturb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 10 publications
(11 reference statements)
0
17
0
Order By: Relevance
“…Axial motion can be tracked by placement of a phase reference object near the sample, such as a coverslip or catheter sheath, so that it appears in the OCT image [141,144]. Using this reference object, the phase of each A-line can be aligned in post-processing to restore phase stability.…”
Section: Hardware Methods For Phase Stabilizationmentioning
confidence: 99%
“…Axial motion can be tracked by placement of a phase reference object near the sample, such as a coverslip or catheter sheath, so that it appears in the OCT image [141,144]. Using this reference object, the phase of each A-line can be aligned in post-processing to restore phase stability.…”
Section: Hardware Methods For Phase Stabilizationmentioning
confidence: 99%
“…Some authors use this approach combined with cross-correlation to improve sensitivity of the OCT system [79]. One study used the group velocity and phase of a common scatterer to stabilize the system before solving the inverse problem of interferometric synthetic aperture microscopy (ISAM) [80]. Figure 13.9 shows an example where phase correction was applied using a coverslip as a phase reference.…”
Section: Motion and Phasementioning
confidence: 99%
“…Spatial oversampling is necessary to separate out the static sample structure from the moving scatterers within the sample. In OMAG, for instance, the separation is obtained by applying a constant Images used with permission from [80]. The plots show the group delay and phase as a function of transverse position on the coverslip interface carrier frequency during B-scan acquisition, and a subsequent Hilbert transform is used to separate out the moving scatterers from the static tissue structure [68].…”
Section: Motion and Phasementioning
confidence: 99%
“…Interferometric Synthetic Aperture Microscopy (ISAM) [10], Computational Adaptive Optics (CAO) [11], Digital Adaptive Optics (DAO) [12], and Holoscopy [13] are all computed imaging techniques which can computationally correct defocus and optical aberrations, but are known to have especially high sensitivity to motion [14][15][16]. This is true for even the swept-source full-field techniques (DAO and Holoscopy).…”
Section: Introductionmentioning
confidence: 99%
“…We show that combined, these techniques are sensitive enough to correct 3-D motion for in vivo numerical defocus and aberration correction. Previous work typically required either stable data at the time of imaging [17,18], or a phase reference was used, such as a coverslip placed on the sample or tissue, to compensate for optical path length fluctuations [14]. Additionally, other efforts have shown that motion could be corrected by using only the acquired OCT data for numerical defocus correction and other phase-resolved techniques [19,20].…”
Section: Introductionmentioning
confidence: 99%